Demonstrations Aspirations Regarding May Day Resignation - Franciska Chika Bella; Yunni Widhi Astuti; Salsa Bila Juita; Reisa Indira; Oktaviani Puspitasari Ayuningtyas; Zahra Nurizki Widyasari (Universitas Muhammadiyah Surakarta, 2022)
International Labor Day is known as May Day which is celebrated on May 1 around the world. This commemoration originated from the trade union movement to celebrate the economic and social success of the workers. With the existence of a labor day, it is expected to get an additional day off, but it is considered to be included and gets paid. Problems that often arise in the world of labor include violence, such violence is an act outside the morals of humanity. Even the perpetrators can be punished. Another problem that is often demanded by workers is the abolition of the out sourcing system, this system is considered to be detrimental to the position of workers, especially cuts in workers' salaries. The basic problem for workers is the issue of salaries that are not commensurate with the needs of a decent living. Related to the sequence of workers, the government and employers should pay more attention to the wages of workers. In the aspirations or desires of workers, the demands submitted by workers can find out what the government can take when workers submit their aspirations in the covid and non-covid era. Labor participation in demonstrations as a strategy formed by workers in an effort to solve collective problems. The reason for the increase in cooking oil is due to hoarding, the diversion of sales from modern retail to traditional markets. The impact of the problems related to the scarcity and increase in the price of basic commodities above, the government needs to issue a policy related to the stability of staple food prices in Indonesia, this is needed to maintain market stability and to anticipate panic buying by the public, especially before the preparation for Eid al-Fitr, and demands that President Jokowi revoke the trade minister who is considered to have failed to control prices. cooking oil and other staples. With regard to workers, the government and employers should pay more attention to labor matters.